Whither Non-Alignment? Indian Ocean Zone of Peace and New Delhi's Selective Alignment with Great Powers during the Cold War, 1964–1979. Issue 1 (2nd January 2019) - Joshi, Yogesh
ABSTRACT: First proposed in 1964 by the Sri Lankan prime minister, the Indian Ocean Zone of Peace [IOZP] entailed eradication of foreign military bases from the Indian Ocean region as well its denuclearisation. During the Cold War, India was one of the most vehement supporters of IOZP. If some saw India's interests in the IOZP as another manifestation of Nehruvian idealism, others viewed it as a part of its non-aligned foreign policy. This analysis argues otherwise. India's record on IOZP reveals a policy of selective alignment with Great Powers and its adaptation to the principles of power politics in international relations. India's support for the presence of one or the other Great Powers in the Indian Ocean region found premise on balancing those it considered hostile to its national security interests. In public, India supported the call for IOZP as dictated by its non-aligned foreign policy; privately, New Delhi remained highly sceptical and often worked to IZOP's detriment. Under the cloak of IOZP, India not only pursued diplomatic alignment with Great Powers but also ensured that its own regional ambitions remain unchecked. In this picture, India's role was not only supportive of the Cold War but to the extent it could use the opportunities provided by superpower rivalry in the region to further its own ends, even determinative of the process.